Development of an off-axis digital holographic microscope for large scale measurement in fluid mechanics - Tamrin K. F., Rahmatullah Bahbibi, Samuri S. M. (N/A, 2014)
Development of an off-axis digital holographic microscope for large scale measurement in fluid mechanics by Tamrin K. F., Rahmatullah Bahbibi, Samuri S. M.,